Pengembangan Modul Ajar PKn Kurikulum Merdeka di Kelas V Sekolah Dasar - Imron, Meitha Rahmawati; Mivtha Citraningrum; Mustika irianti (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research is a Research And Development (R&D) research with a 4-D model modified into 3-D, with 3 stages of research, namely Define, Design, and Develop. Class V students of SD Inpres 28 Sorong Regency totaling 26 students are the subjects in this study. The instrument used is a questionnaire to obtain validation results from validators. The results of this study show that the teaching module of the Independent Curriculum Pkn class V with learning unit 1 "Exemplary in Pancasila" With the theme "History of the birth of Pancasila and its formulators" is included in the very valid category with an average score of 100% based on validity test data by validators, media experts, and material experts so that it is suitable to be used to support the learning process. The results of the plasticity test of the teaching module of the Independent Curriculum Independent Curriculum class V with learning unit 1 "Exemplary in Pancasila" With the theme "The history of the birth of Pancasila and its formulators" indicates that the module is included in the very practical category with an average score of 94.5% of the teacher's response percentage and the average value of the student's response percentage, namely 91% This shows that the teaching module of the Independent Curriculum Pkn in grade V is very practical and very valid